Self-construction in a district of the province of Huancayo, Junín, Peru - Nieva Villegas, Mayda Alvina (2021)
The present research aims to analyze the development of the complex process of self-construction for the occupation of houses in the district of Chilca - Huancayo, it has a quantitative-qualitative approach with a descriptive, cross-retrospective design. A non-probabilistic sample of self-built homeowners was selected from a block in the Puzo neighborhood, in the Chilca district. The research methodology was analytical in scope and empirical level method, it was used as data collection instruments: technical sheets on the houses and semi-structured interviews with the owners. The results showed that self-construction is a real situation that has gradually increased in the Chilca district and it is necessary to know more about this process to propose actions, policies and responsibilities. The study concluded that in the technical-construction aspect, advice on the matter, quality control of construction materials, and adequate planning and organization of the execution of the work should be carried out. In addition, on the social aspect, there is little information that can contribute to the knowledge of the population, since habits and customs largely define this self-constructive process, the heads of families have rural experience, where housing is only seen as a necessity family shelter.